REGIONAL DIFFERENCES IN AGRICULTURE IN SLOVAKIA AFTER ITS ACCESSION TO THE EUROPEAN UNION - Némethová, Jana; Civáň, Marek (Quaestiones Geographicae, 2017)
The Common Agricultural Policy of the European Union is reflected in the development of agricultural production in Slovakia. The development of livestock production faced significant changes reflected in its overall decrease. The decrease in the level of agricultural production in Slovakia between 2002 and 2010 is shown by several indicators assessed in this paper. Its main aim is to highlight differences in Slovak agriculture at the level of LAU I, which are districts of Slovakia, according to the selected indicators of agricultural production between 2002 and 2010. We analyse the development of regional differences in Slovak agriculture that have widened under the influence of the EU Common Agricultural Policy. The development of selected indicators of agricultural production was analysed using the change index, which best represents differences in the development of agriculture in the Slovak regions.